(untitled) (Latakia University Journal - Arts and Humanities Sciences Series, 2023)
The research aims to identify the level of environmental responsibility among managers and workers in private business enterprises in the city of Lattakia, and to identify the differences in the level of environmental responsibility in private business enterprises in the city of Lattakia depending on the variables (the nature of the enterprise’s work – the size of the enterprise), and to achieve the research goal, the researcher built a questionnaire consisting of (19) items and distributed in three dimensions, which are (after environmental commitments, resource and energy management, after participation effective for stakeholders), and its validity and reliability were confirmed, and then applied to a sample consisting of (60) individual managers and workers, and the research sample included (12) private business establishments in the city of Lattakia, and the results of the research showed that the level of environmental responsibility among managers and workers in private business establishments in the city of Lattakia come to a medium degree, and the results also showed that there were statistically significant differences between the mean scores of the members of the research sample on the environmental responsibility questionnaire according to the variable of the nature of the enterprise’s work, and the absence of Statistically significant differences between the mean scores of the members of the research sample on the environmental responsibility questionnaire according to the variable of the size of the institution, and the research has many proposals, the most important of which are: dissemination of a culture of sustainable protection of the environment among managers and workers in private business enterprises that seek to preserve the environment and continue to achieve profits for the enterprise.